Catalyst-Free One-Pot Synthesis of Novel Heteroarylamine Substituted Furo[3,2-c]coumarins - Olyaei, Abolfazl; Saraei, Mahnaz; Khoeiniha, Reyhaneh (Synlett, 2018)
A high-yielding cyclocondensation of 4-hydroxycoumarin, phenylglyoxal monohydrate, and heteroarylamines proceeds without catalysis, which gives novel functionalized furo[3,2-c]coumarins and heteroarylamino alkylation of coumarin products in acetonitrile under reflux, is reported for the first time. This tandem process involves sequentially an aldol condensation, Michael addition, a ring closure, and dehydration reaction.
Keywords: furo[3,2-c]coumarin; phenylglyoxal monohydrate; 4-hydroxycoumarin; heteroarylamine; multicomponent reaction